2017
DOI: 10.1007/s10103-017-2406-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific effects and clusters of women with painful TMD responders and non-responders to LLLT: double-blind randomized clinical trial

Abstract: The aim was to analyze the non-specific effects (placebo, spontaneous remission, and regression to the mean) of the low-level laser therapy (LLLT) in women with myofascial pain (painful temporomandibular disorder (TMD)), as well as to differentiate between responders and non-responder clusters to active and placebo LLLT according to the anxiety levels, salivary cortisol, use of oral contraceptives, and premenstrual period. Sixty-four women diagnosed with myofascial pain (Research Diagnostic Criteria for Tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 33 publications
0
32
0
6
Order By: Relevance
“…46,48 Collecting information of these heterogeneous clinical trials showed beneficial impacts of PBM on reducing pain at the shortterm follow-up (10 days to 4 weeks) both in the visual analog scale 36 and in the anxiety questionnaire. 46,47,[55][56][57] Among these studies, GaAlAs diode at 780 nm wavelength and 50 mW power showed the most frequent nonsignificant effects. 58,59 Functionality of TMJ was assessed in terms of maximum opening, electromyography, geometric mean diameter, colorimetric capsule method, and craniomandibular index, indicating that the total effect favored PBM in comparison with placebo.…”
Section: Indications Of Pbm For Tmdsmentioning
confidence: 99%
“…46,48 Collecting information of these heterogeneous clinical trials showed beneficial impacts of PBM on reducing pain at the shortterm follow-up (10 days to 4 weeks) both in the visual analog scale 36 and in the anxiety questionnaire. 46,47,[55][56][57] Among these studies, GaAlAs diode at 780 nm wavelength and 50 mW power showed the most frequent nonsignificant effects. 58,59 Functionality of TMJ was assessed in terms of maximum opening, electromyography, geometric mean diameter, colorimetric capsule method, and craniomandibular index, indicating that the total effect favored PBM in comparison with placebo.…”
Section: Indications Of Pbm For Tmdsmentioning
confidence: 99%
“…Moreover, the absence of a significant difference between groups leads to the assumption that non‐specific factors may have influenced treatment outcomes. Among these, the placebo effect has been considered very important, mainly in acupuncture clinical trials because of individual psychosocial factors that modify biochemistry and neural circuits 45,46 . Hence, the placebo effect as well as other unspecific factors such as natural history and regression to the mean could not be ruled out in this study.…”
Section: Discussionmentioning
confidence: 97%
“…The post-extraction sockets 18,19 (even if a first intention closure is performed), periodontal surgery and implantology 20 , orthodontics 21,22 , temporomandibular joints disorders, and neurological conditions may all benefit from superficial irradiation in which part of the laser beam penetrates a deeper level 23,24 .…”
Section: Discussionmentioning
confidence: 99%